The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/420844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyacrylamide Bead Sensors for in vivo Quantification of Cell-Scale Stress in Zebrafish Development

Abstract: Mechanical stress exerted and experienced by cells during tissue morphogenesis and organ formation plays an important role in embryonic development. While techniques to quantify mechanical stresses in vitro are available, few methods exist for studying stresses in living organisms. Here, we describe and characterize cell-like polyacrylamide (PAAm) bead sensors with well-defined elastic properties and size for in vivo quantification of cell-scale stresses. The beads were injected into developing zebrafish embry… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Moreover, we have shown that NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-019-13804-z ARTICLE the dynamics of such processes can be captured using live cells and time-lapse microscopy, and can be correlated with cellular protein distributions. As also exemplified by the development of an analogous approach for quantifying forces during development in zebrafish embryos by Träber et al 40 , the method presented here is expected to be broadly applicable in the study of inter-and intracellular forces in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, we have shown that NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-019-13804-z ARTICLE the dynamics of such processes can be captured using live cells and time-lapse microscopy, and can be correlated with cellular protein distributions. As also exemplified by the development of an analogous approach for quantifying forces during development in zebrafish embryos by Träber et al 40 , the method presented here is expected to be broadly applicable in the study of inter-and intracellular forces in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Bulk modulus measurements. Bulk modulus measurements were performed as described previously 40,44 . Briefly, dextran solutions with known osmotic pressure 45 were made from FITC-conjugated dextran (molecular weight: 2 × 10 6 g/mol, Mil-liporeSigma 52471).…”
Section: ) or Tetramethylrhodamine Cadaverine For All Other Experimenmentioning
confidence: 99%
“…As also exemplified by the development of an analogous approach for quantifying forces during development in zebrafish embryos by Träber et al 36 , the method presented here is expected to be broadly applicable in the study of inter-and intracellular forces in vitro and in vivo.…”
Section: Live-cell Force Dynamics Within the Cytotoxic T Cell Immunolmentioning
confidence: 95%
“…To determine the local tension in the muscle tissue, we implemented elastic hydrogel beads as tension sensors, an approach first used by others in different systems [13,28,53,55]. We custom-made elastic PAA beads by a water in oil emulsion approach ( Figure 3A).…”
Section: Characterization and Computational Analysis Of Elastic Paa Bmentioning
confidence: 99%
“…Despite this, non-destructive experimental approaches to investigate spatial and temporal forces on a cellular level are limited and thus, characterization of local cell niches within a tissue remains a challenge. To overcome this problem, Campas et al introduced 2/23 biocompatible oil microdroplets to evaluate cell-generated forces in living tissue for the first time [10] and very recently, deformable PAA beads were used to determine local tension on a cell scale within cancer spheroids, zebrafish embryos and during phagocytosis [13,28,53,55]. Contrary to oil microdroplets, PAA beads are compressible and are therefore able to reveal isotropic tissue pressure.…”
Section: Introductionmentioning
confidence: 99%